Kepuasan Pasien Rawat Inap Rumah Sakit Dipengaruhi Oleh Mutu Pelayanan Keperawatan - Olga Jadha Casmira; Edi Sukamto; Hesti Prawita Widiastuti (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
At the hospital, the most contributing resources are supporting patients, one of whom is a nurse. Nurses have a big influence to determine the quality of service. The nurse is the spearhead of services to patients and their families at the Hospital, because of the frequency of meetings with patients who are most often. The purpose of this study was to prove that there is a relationship between the quality of nursing services and patient satisfaction at Abdul Wahab Sjahranie Hospital SamarindaThis study is a quantitative study, the study design used descriptive analytical with cross sectional approach. The population is 323 people spread from 8 inpatient units. The sample of 67 people used purposive sampling technique. The instrument in this study used a questionnaire that contained indicators of the quality of nursing services related to inpatient satisfaction. The scale used is a Likert scale to assess the quality of nursing services provided and to assess patient satisfaction using the Guttman scale. The results showed that there was a relationship between the quality of nursing services and patient satisfaction (p value = 0.001). The results of this study are expected to be a source of information for students to know more about the quality of nursing services.